1995
DOI: 10.1182/blood.v85.6.1517.bloodjournal8561517
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of factor XIa in human plasma assessed by measuring factor XIa-protease inhibitor complexes: major role for C1-inhibitor

Abstract: From experiments with purified proteins, it has been concluded that factor XIa (FXIa) is inhibited in plasma mainly by alpha 1-antitrypsin (a1AT), followed by antithrombin III (ATIII), C1-inhibitor (C1Inh), and alpha 2-antiplasmin (a2AP). However, the validity of this concept has never been studied in plasma. We established the relative contribution of different inhibitors to the inactivation of FXIa in human plasma, using enzyme-linked immunosorbent assays (ELISAs) for the quantification of complexes of FXIa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 1 publication
3
96
1
1
Order By: Relevance
“…by assessment of the generation of complexes of C1inhibitor and activated FXIIa, factor XIa and kallikrein. Since C1-inhibitor is the major inhibitor in plasma of all three proteases of the contact system (Schapira et al, 1982;Pixley et al, 1985;Wuillemin et al, 1995), the generation of protease-C1-inhibitor complexes reflected the contact system activation in plasma (Nuijens et al, 1987;Lewin et al, 1983;Kaplan et al, 1985;Wuillemin et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by assessment of the generation of complexes of C1inhibitor and activated FXIIa, factor XIa and kallikrein. Since C1-inhibitor is the major inhibitor in plasma of all three proteases of the contact system (Schapira et al, 1982;Pixley et al, 1985;Wuillemin et al, 1995), the generation of protease-C1-inhibitor complexes reflected the contact system activation in plasma (Nuijens et al, 1987;Lewin et al, 1983;Kaplan et al, 1985;Wuillemin et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Sample dilutions were tested in duplicate and the concentrations of FXIIa-C1-inhibitor and kallikrein-C1-inhibitor complexes generated were calculated by comparison with normal pooled human plasma fully activated by DS500 (50 mg/ml) (Nuijens et al, 1988). Generation of factor XIa-C1-inhibitor complexes was determined by an enzyme-linked immunosorbent assay (ELISA) using kaolin-activated normal plasma as an in-house standard (Wuillemin et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in greater detail in the Pathogenesis and Pathobiology of HAE and AAE section, C1-INH controls several proteases, including C1r and C1s, the mannosebinding protein associated serine protease (MASP) system, kallikrein, coagulation factors XIIa and XIa, plasmin, and tissue plasminogen activator. [139][140][141][142][143][144] Therefore, C1-INH plays a key role in regulating the early steps of complement and the contact system of kinin formation. 89 This broad inhibitory ability ensues from a property unique to the serpin class: highly efficient complex formation with target proteases.…”
Section: Aae: Further Distinctionsmentioning
confidence: 99%
“…Few studies have attempted to measure bradykinin according to such protocols in HAE, but these studies have shown increased bradykinin generation during attacks and not during symptom-free periods, particularly when samples are drawn from the site of the edematous swelling. 13,14,27 C1-INH is a major inhibitor of factor XIa of the intrinsic pathway of the intrinsic pathway of coagulation 143,224 and also inhibits thrombin, 199 although inhibition of this latter enzyme is likely physiologically inconsequential. The role of factor XI in coagulation is not yet resolved.…”
Section: Pathogenesis Of Angioedema Attacksmentioning
confidence: 99%
“…Upon activation in plasma, factor XI forms complexes with several protease inhibitors, the dominant inhibitor being C1-inhibitor (Wuillemin et al, 1995). Hence, to assess activation of factor XI in the patients, levels of factor XIa± C1-inhibitor complexes were measured according to a method described previously (Wuillemin et al, 1995). In the plasma of normal volunteers, levels of these complexes are below the detection limit (10 pmol/l) of this assay.…”
Section: Methodsmentioning
confidence: 99%